THE INTEGRATION OF EFFECTIVE TEACHING METHODS AND MODERN TECHNOLOGIES FOR THE FORMATION OF THE XXI CENTURY SKILLS - Ogay, Mukaddaskhon (Журнал иностранных языков и лингвистики, 2021)
The purpose of this work is to consider the educational opportunities of modern information technologies, as well as to identify effective modern methods of teaching English in the education system of the Republic of Uzbekistan.